Modified elastomer composition, crosslinked elastomer composition and molded article thereof
A modified elastomer composition with ethylene/α-olefin/non-conjugated diene copolymer and polypropylene enhances compression set and moldability, addressing the limitations of thermoplastic and thermosetting rubbers for improved durability and sealing applications.
Patent Information
- Application Number
- JP2019034532
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-02-27
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2039-02-27
AI Technical Summary
Existing thermoplastic elastomers have inadequate compression set properties and moldability, while thermosetting rubbers face issues with long crosslinking processes and poor durability, limiting their applications in sealing and other demanding environments.
A modified elastomer composition comprising ethylene/α-olefin/non-conjugated diene copolymer rubber, ethylene/α-olefin copolymer rubber, modified polypropylene with strain hardening properties, and an unsaturated silane compound, crosslinked using a silanol condensation catalyst, to achieve improved compression set, moldability, and surface appearance.
The composition achieves compression set characteristics comparable to thermosetting rubbers with the moldability of thermoplastic elastomers, suitable for applications requiring good rubber elasticity and durability.
Smart Images

Figure 0007603369000001 
Figure 0007603369000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a modified elastomer composition, a crosslinked elastomer composition, and a molded article thereof. More specifically, the present invention relates to a novel modified elastomer composition and crosslinked elastomer composition excellent in compression set, moldability, and surface appearance, and a molded article using the same. [Background technology]
[0002] Thermoplastic elastomers are elastomers that soften and become fluid when heated, and have rubber elasticity when cooled. Thermoplastic elastomers have the same moldability as thermoplastic resins, as well as rubber elasticity, and are recyclable, so they are widely used in automobile parts, building parts, medical parts, electric wire coating materials, miscellaneous goods, etc.
[0003] When used in applications requiring sealing properties, it is important to have good rubber elasticity, compression set properties, and good moldability, and much research has been done to achieve this, but because thermoplastic elastomers contain thermoplastic resins such as polyolefins to ensure thermoplasticity, their compression set properties are insufficient compared to thermosetting rubber, limiting the applications in which they can be used. On the other hand, thermosetting rubbers such as EPDM have excellent compression set properties, but they require a long crosslinking process and have the disadvantage of being inferior in durability.
[0004] For example, Patent Documents 1 to 3 propose silane-modified elastomer compositions with improved compression set, but a large amount of unsaturated silane compound must be added to improve the compression set properties, which causes problems in terms of economy and productivity. In addition, the material has a high gloss, making it unsuitable for sealing materials, and there is also a problem that it is prone to blocking during or after pelletization. Patent Document 4 also proposes a silane-modified elastomer composition, but the compression set (70°C x 22 hours) was only slightly over 50%, which was insufficient. Patent Document 5 proposes a dynamically crosslinked thermoplastic elastomer composition using a crosslinking agent such as a phenolic resin, but as mentioned above, the components contain a non-crosslinked thermoplastic resin, so the compression set properties are insufficient. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2016 / 140251 [Patent Document 2] International Publication No. 2016 / 140252 [Patent Document 3] International Publication No. 2016 / 140253 [Patent Document 4] Patent No. 5346285 [Patent Document 5] Special Publication No. 2005-516098 Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made in view of the above problems, and an object of the present invention is to provide a novel elastomer composition which can be used in a molding machine for thermoplastic elastomers and which has excellent compression set, moldability and surface appearance. [Means for solving the problem]
[0007] As a result of intensive research conducted by the present inventors to solve the above-mentioned problems, they have found that a modified elastomer composition obtained by graft-modifying a polypropylene resin, in particular a modified polypropylene exhibiting strain hardening properties, with an ethylene-α-olefin-non-conjugated diene copolymer rubber, an ethylene-α-olefin copolymer rubber not containing non-conjugated diene units, and a composition containing an unsaturated silane compound, or a crosslinked elastomer composition obtained by further crosslinking the modified elastomer composition, can have compression set properties equivalent to thermosetting rubber and moldability and surface appearance equivalent to thermoplastic elastomers, which were originally thought to be impossible, and have thus completed the present invention. That is, the gist of the present invention lies in the following [1] to
[10] .
[0008] [1] A modified elastomer composition comprising the following components (A) to (D) and grafted with the following component (E): Component (A): Ethylene / α-olefin / non-conjugated diene copolymer rubber Component (B): Ethylene-α-olefin copolymer rubber that does not contain non-conjugated diene units Component (C): Modified polypropylene exhibiting strain hardening, with a melt flow rate of 1.0 g / 10 min or more (230°C, load 21.2 N, JIS K7210 compliant) and a melt tension of 3.0 cN or more. Component (D): Unsaturated silane compound Component (E): Peroxide
[0009] [2] The modified elastomer composition according to [1], wherein the component (A) is 5 to 40 parts by mass per 100 parts by mass of the total of the components (A), (B), and (C), the component (B) is 30 to 90 parts by mass per 100 parts by mass of the total of the components (A), (B), and (C), the component (C) is 5 to 30 parts by mass per 100 parts by mass of the total of the components (A), (B), and (C), and the component (D) is 0.01 to 5 parts by mass per 100 parts by mass of the total of the components (A), (B), and (C).
[0010] [3] The modified elastomer composition according to [1] or [2], wherein the amount of the component (E) used is 0.01 to 3 parts by mass per 100 parts by mass of the total of the components (A), (B) and (C).
[0011] [4] The density of the component (B) is 0.880 g / cm 3 The modified elastomer composition according to any one of [1] to [3], which is:
[0012] [5] The modified elastomer composition according to any one of [1] to [4], further comprising a component (F): a crosslinking auxiliary, in an amount of 0.001 to 2 parts by mass per 100 parts by mass of the total of the components (A), (B) and (C).
[0013] [6] The modified elastomer composition according to any one of [1] to [5], wherein the component (B) has a melting end peak temperature of 115°C or higher as measured by a differential scanning calorimeter (DSC).
[0014] [7] The modified elastomer composition according to any one of [1] to [6], wherein the component (D) is a compound represented by the following formula (1): RSi(R')3…(1) (wherein R is an ethylenically unsaturated hydrocarbon group, R' are each independently a hydrocarbon group having 1 to 10 carbon atoms or an alkoxy group having 1 to 10 carbon atoms, and at least one of the R' is an alkoxy group having 1 to 10 carbon atoms.)
[0015] [8] The modified elastomer composition according to any one of [1] to [7], further comprising component (G): a softener, in an amount of 0.5 to 200 parts by mass per 100 parts by mass of the total of component (A), component (B) and component (C).
[0016] [9] A crosslinked elastomer composition obtained by subjecting the modified elastomer composition according to any one of [1] to [8] to a crosslinking reaction using component (H): a silanol condensation catalyst.
[0017]
[10] A molded article obtained by molding the modified elastomer composition according to any one of [1] to [8] or the crosslinked elastomer composition according to [9]. Effect of the Invention
[0018] According to the present invention, it is possible to provide a modified elastomer composition and a crosslinked elastomer composition which are excellent in compression set characteristics, moldability and surface appearance, and a molded article using the same. The modified elastomer composition and crosslinked elastomer composition of the present invention, as well as molded articles using the same, are expected to be used in applications requiring good rubber elasticity in which thermosetting rubbers have been conventionally used, as well as in various applications exposed to harsh usage environments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The following describes in detail the embodiments of the present invention, but the present invention is not limited to the following description, and can be modified as desired without departing from the gist of the present invention. In this specification, when a numerical value or physical property value is enclosed before and after "~", the value before and after the "~" is included.
[0020] [Modified elastomer composition] The modified elastomer composition of the present invention is a modified elastomer composition comprising the following components (A) to (D) and grafted with the following component (E), and preferably further comprising the following components (F) to (G): Component (A): Ethylene / α-olefin / non-conjugated diene copolymer rubber Component (B): Ethylene-α-olefin copolymer rubber that does not contain non-conjugated diene units Component (C): Modified polypropylene exhibiting strain hardening, having a melt flow rate of 1.0 g / 10 min or more (230°C, load 21.2 N, JIS K7210 compliant) and a melt tension of 3.0 cN or more. Component (D): Unsaturated silane compound Component (E): Peroxide Component (F): Crosslinking agent Component (G): Softener
[0021] [Crosslinked elastomer composition] The crosslinked elastomer composition of the present invention is obtained by subjecting the above-mentioned modified elastomer composition to a crosslinking reaction with the following component (H). Component (H): Silanol condensation catalyst
[0022] <Mechanism> The mechanism by which the modified elastomer composition and crosslinked elastomer composition of the present invention exhibit the effects of excellent compression set characteristics, moldability and good surface appearance is presumed to be as follows. By finely dispersing component (A) in component (B), crosslinking proceeds uniformly and local crosslinking is suppressed, resulting in a reduction in the number of lumps. Furthermore, since there are no residual double bonds, good physical properties can be obtained. In addition, the strain hardening property of component (C) holds components (A) and (B) as a fluidized bed, resulting in good moldability, and therefore excellent extrusion appearance. Furthermore, the particle size of component (A) can be reduced during the dynamic heat treatment stage, resulting in good rubber elasticity.
[0023] <Component (A): Ethylene / α-olefin / non-conjugated diene copolymer rubber> The ethylene-α-olefin-non-conjugated diene copolymer rubber of component (A) is a copolymer containing ethylene, α-olefin, and a non-conjugated diene compound as copolymerization components. Ethylene-α-olefin-non-conjugated diene copolymer rubber includes oil-extended type rubber, which is a mixture of ethylene-α-olefin-non-conjugated diene copolymer rubber and a hydrocarbon-based rubber softener (hereinafter, also referred to as "oil-extended ethylene-α-olefin-non-conjugated diene copolymer rubber"), and non-oil-extended type rubber, which does not contain a hydrocarbon-based rubber softener. In this embodiment, the oil-extended type copolymer rubber is intended, but the non-oil-extended type rubber can also be suitably used. That is, in the present invention, the ethylene-α-olefin-non-conjugated diene copolymer rubber of component (A) may be either an oil-extended type or a non-oil-extended type, and either a single type of the non-oil-extended type or an oil-extended type may be used alone, or two or more types may be used in any combination and ratio, or one or more types of the oil-extended type and one or more types of the non-oil-extended type may be used in any combination and ratio. In the case of the oil-extended type, the hydrocarbon-based rubber softener contained in the mixture is classified as a softener of component (G).
[0024] Examples of the hydrocarbon-based rubber softener contained in the oil-extended type include those exemplified as component (G) described below. In addition, in a mixture of oil-extended type ethylene-α-olefin-non-conjugated diene copolymer rubber and a hydrocarbon-based rubber softener, the ratio of the hydrocarbon-based rubber softener (oil extension amount) to 100 parts by mass of the oil-extended type ethylene-α-olefin-non-conjugated diene copolymer rubber is usually about 0.5 to 200 parts by mass.
[0025] Examples of the α-olefin in component (A) include α-olefins having 3 to 20 carbon atoms, more preferably 3 to 8 carbon atoms, such as propylene, 1-butene, 3-methyl-1-butene, 1-pentene, 4-methyl-1-pentene, 4,4-dimethyl-1-pentene, 1-hexene, 4-methyl-1-hexene, 1-heptene, 1-octene, 1-decene, and 1-octadecene, but are not particularly limited thereto. Among these, from the viewpoint of crosslinkability and bloom-out suppression, propylene, 1-butene, 3-methyl-1-butene, and 1-pentene are preferred, and propylene and 1-butene are more preferred. The α-olefins can be used alone or in any combination and ratio of two or more kinds.
[0026] The non-conjugated diene compounds in component (A) include dicyclopentadiene, 1,4-hexadiene, cyclohexadiene, cyclooctadiene, dicyclooctadiene, 1,6-octadiene, 5-methyl-1,4-hexadiene, 3,7-dimethyl-1,6-octadiene, 1,3-cyclopentadiene, 1,4-cyclohexadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, Examples of the non-conjugated diene include, but are not limited to, 5-isopropylidene-2-norbornene, 5-vinyl-2-norbornene, vinylidene norbornene, 5-ethylidene-2-norbornene (ENB) and other ethylidene norbornenes, and 5-methylene-2-norbornene (MNB) and other methylene norbornenes. Among these, from the viewpoint of crosslinkability, dicyclopentadiene, ethylidene norbornene, and vinylidene norbornene are preferred, and dicyclopentadiene, 5-ethylidene-2-norbornene, and vinylidene norbornene are more preferred. The non-conjugated diene may be used alone or in any combination and ratio of two or more types.
[0027] Specific examples of ethylene-α-olefin-non-conjugated diene copolymer rubber include ethylene-propylene-5-ethylidene-2-norbornene copolymer rubber, ethylene-propylene-dicyclopentadiene copolymer rubber, ethylene-propylene-1,4-hexadiene copolymer rubber, ethylene-propylene-5-vinyl-2-norbornene copolymer rubber, and other ethylene-propylene-non-conjugated diene copolymer rubbers (EPDM), and ethylene-1-butene-5-ethylidene-2-norbornene copolymer rubber, but are not limited thereto. Among these, ethylene-propylene-non-conjugated diene copolymer rubber (EPDM) is preferred from the viewpoint of crosslinking property and bloom-out suppression. The ethylene-α-olefin-non-conjugated diene copolymer rubber can be used alone or in any combination and ratio of two or more kinds.
[0028] The content of ethylene units in the ethylene-α-olefin-non-conjugated diene copolymer rubber is not particularly limited, but is preferably 50 to 90 mass%, more preferably 55 to 85 mass%, and further preferably 60 to 80 mass%. When the content of ethylene units is within the above preferred range, an elastomer composition having excellent mechanical strength and rubber elasticity tends to be obtained.
[0029] The content of the α-olefin unit in the ethylene-α-olefin-non-conjugated diene copolymer rubber is not particularly limited, but is preferably 10 to 50 mass%, more preferably 15 to 45 mass%, and further preferably 20 to 40 mass%. When the content of the α-olefin unit is within the above preferred range, an elastomer composition excellent in mechanical strength, moderate flexibility, and rubber elasticity tends to be obtained.
[0030] Furthermore, the content of the non-conjugated diene unit in the ethylene-α-olefin-non-conjugated diene copolymer rubber is not particularly limited, but is preferably 0.5 to 30 mass%, more preferably 1 to 20 mass%, and even more preferably 2 to 10 mass%. When the content of the non-conjugated diene unit is within the above-mentioned preferred range, it becomes easy to adjust the crosslinkability and moldability, and an elastomer composition having excellent mechanical strength and rubber elasticity tends to be easily obtained.
[0031] The contents of the structural units of component (A) and components (B), (C), and (D) described below can be determined by infrared spectroscopy.
[0032] In the present invention, the component (A) is preferably an ethylene-propylene-non-conjugated diene copolymer rubber having an ethylene unit content of 55 to 75 mass%, a propylene unit content of 15 to 40 mass%, and a content of at least one non-conjugated diene unit selected from the group consisting of dicyclopentadiene, 5-ethylidene-2-norbornene, and vinylidenenorbornene of 1 to 10 mass%.
[0033] The ethylene / α-olefin / non-conjugated diene copolymer rubber of component (A) may be used singly or in any combination and ratio of two or more kinds.
[0034] <Component (B): Ethylene / α-olefin copolymer> The ethylene-α-olefin copolymer of component (B) is a copolymer containing ethylene units and α-olefin units and not containing non-conjugated diene units, i.e., an ethylene-α-olefin copolymer other than component (A). The type of the ethylene-α-olefin copolymer of component (B) is not particularly limited so long as it is of this type, and any known ethylene-α-olefin copolymer may be appropriately used.
[0035] Specific examples of the ethylene-α-olefin copolymer include copolymers of ethylene and one or more α-olefins having 3 to 10 carbon atoms, such as ethylene-propylene copolymer, ethylene-1-butene copolymer, ethylene-4-methyl-1-pentene copolymer, ethylene-1-hexene copolymer, and ethylene-1-octene copolymer.
[0036] The type of catalyst used in producing the ethylene-α-olefin copolymer is not particularly limited, but examples thereof include Ziegler-Natta catalysts and metallocene catalysts. Among these, ethylene-α-olefin copolymers produced using a metallocene catalyst are preferred.
[0037] The ethylene-α-olefin copolymer used in the present invention preferably has a melting end peak temperature (hereinafter sometimes referred to as "melting end point") of 115°C or higher as measured by a differential scanning calorimeter (DSC). If the melting end point of the ethylene-α-olefin copolymer is 115°C or higher, the copolymer can maintain its shape due to crystallization even at high temperatures. From this viewpoint, the melting end point of the ethylene-α-olefin copolymer is preferably 115°C or higher. However, if the melting end point of the ethylene-α-olefin copolymer is excessively high, there is a risk of poor appearance due to unmelted particles during heating during molding and early crystallization (melt fracture) during cooling during molding. Therefore, the melting end point of the ethylene-α-olefin copolymer is usually 145°C or lower. The melting end point of the ethylene-α-olefin copolymer is measured by the method described in the Examples section below.
[0038] The density of the ethylene-α-olefin copolymer of component (B) used in the present invention (measured according to JIS K6922-1,2:1997) is 0.850 to 0.910 g / cm 3 and more preferably 0.860 to 0.900 g / cm 3 , more preferably 0.860 to 0.880 g / cm 3When the density is equal to or less than the upper limit, the material tends to be flexible and have excellent sealing performance, whereas when the density is equal to or more than the lower limit, the material tends to be able to maintain its shape at room temperature and has little hysteresis loss, so that the material tends to have excellent resistance to settling.
[0039] The ethylene unit content of the ethylene-α-olefin copolymer of component (B) is preferably at least 50% by mass, more preferably at least 60% by mass. When the ethylene unit content is at least the above lower limit, an elastomer composition having excellent mechanical strength and rubber elasticity tends to be obtained.
[0040] The melt flow rate (MFR) of the ethylene-α-olefin copolymer used in the present invention is measured according to JIS K7210 (1999) at a temperature of 190°C and a load of 21.2N, and is preferably 0.01 to 30g / 10min. If the MFR is too large, the compression set increases, and the sealability may decrease. If the MFR is too small, the motor load during modification extrusion increases, the resin pressure increases, and the productivity decreases, and the surface after molding may become rough. From these viewpoints, the MFR of the ethylene-α-olefin copolymer is more preferably 0.1g / 10min or more, and more preferably 10g / 10min or less.
[0041] The ethylene-α-olefin copolymer used in the present invention can be commercially available, for example, from the Engage (registered trademark) series manufactured by Dow Chemical Company, the Kernel (registered trademark) series manufactured by Japan Polyethylene Corporation, the Infuse (registered trademark) series manufactured by Dow Chemical Company, the Tafmer (registered trademark) series manufactured by Mitsui Chemicals, Inc., and the Evolue (registered trademark) series manufactured by Mitsui Chemicals, Inc.
[0042] The ethylene-α-olefin copolymer of component (B) may be used either alone or in any combination and ratio of two or more kinds.
[0043] <Ingredient (C)> The modified polypropylene of component (C) is a polypropylene-based resin (propylene homopolymer or propylene-based copolymer, hereinafter sometimes referred to as "propylene-based (co)polymer") that exhibits strain hardening. Here, "strain hardening" refers to a phenomenon in which the viscosity increases with an increase in the elongation strain of the molten material. In the present invention, the presence or absence of "strain hardening" can be determined from the breaking behavior of the molten strand when the melt tension is measured under the conditions described below. When the take-up speed is increased, the take-up load increases rapidly and the material is broken, it is determined that the material exhibits strain hardening.
[0044] The modified polypropylene exhibiting strain hardening properties of component (C) has a melt flow rate (MFR, 230° C., load 21.2 N, compliant with JIS K7210) of 1.0 g / 10 min or more and a melt tension of 3.0 cN or more.
[0045] From the viewpoint of moldability, the MFR of the modified polypropylene exhibiting strain hardening of component (C) is preferably 1.5 g / 10 min or more and 100 g / 10 min or less, more preferably 2.0 g / 10 min or more and 70 g / 10 min or less. In particular, from the viewpoint of compression set, the MFR of the modified polypropylene exhibiting strain hardening of component (C) is preferably 50 g / 10 min or less, more preferably 30 g / 10 min or less, and most preferably 10 g / 10 min or less. Here, the MFR of the modified polypropylene exhibiting strain hardening of component (C) is a value measured in accordance with JIS K7210 at 230 ° C. and a load of 2.12 N.
[0046] The melt tension of the modified polypropylene exhibiting strain hardening properties of component (C) is preferably 4.0 to 40 cN, more preferably 5.0 to 35 cN, from the viewpoints of moldability, compression set, and the like.
[0047] Here, the melt tension is measured in the present invention as follows. That is, using a Capillograph (manufactured by Toyo Seiki Seisakusho) equipped with a melt tension measurement attachment and having a φ10 mm cylinder with a φ1 mm, 10 mm long orifice attached to its tip, the strand extruded from the die when the piston was lowered at 230°C with a piston descending speed of 10 mm / min was hung on a pulley equipped with a load cell 350 mm below and taken up at a speed of 1 m / min, and after stabilization, the take-up speed was increased at a rate of reaching 200 m / min in 4 minutes, the load applied to the pulley equipped with the load cell when the strand broke was measured, and this measured load was taken as the melt tension.
[0048] The type of modified polypropylene exhibiting strain hardening property of component (C) is not particularly limited, and any propylene-based copolymer such as a propylene homopolymer, a block copolymer of propylene and other copolymerization components or a random copolymer can be used. Here, the propylene-based copolymer means one having a propylene unit content of more than 50% by mass. From the viewpoint of heat resistance, rigidity, crystallinity, chemical resistance, etc., the propylene unit content in the propylene-based copolymer is preferably 60% by mass or more, more preferably 75% by mass or more, and even more preferably 90% by mass or more. On the other hand, the upper limit is not particularly limited, but is usually less than 100% by mass.
[0049] When the modified polypropylene exhibiting strain hardening property of component (C) is a propylene-based block copolymer or random copolymer, other copolymerization components copolymerized with propylene include α-olefins having 2 or 4 to 12 carbon atoms such as ethylene, 1-butene, 1-butene, 2-methylpropylene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, etc.; cyclic olefins such as cyclopentene, norbornene, tetracyclo[6,2,11,8,13,6]-4-dodecene, etc. Examples of the other copolymerizable components include, but are not limited to, ethylenediamines, dienes such as 5-methylene-2-norbornene, 5-ethylidene-2-norbornene, 1,4-hexadiene, methyl-1,4-hexadiene, and 7-methyl-1,6-octadiene, and vinyl monomers such as vinyl chloride, vinylidene chloride, acrylonitrile, vinyl acetate, acrylic acid, methacrylic acid, maleic acid, ethyl acrylate, butyl acrylate, methyl methacrylate, maleic anhydride, styrene, methylstyrene, vinyltoluene, and divinylbenzene. These other copolymerizable components may be used alone or in any combination and ratio of two or more. Among these, ethylene and 1-butene are preferred.
[0050] When component (C) is a propylene-based block copolymer, it is preferably a propylene-based block copolymer obtained by multi-stage polymerization, such as a propylene-based block copolymer obtained by polymerizing polypropylene in the first stage and polymerizing a propylene-ethylene copolymer in the second stage.
[0051] In addition, as component (C), propylene-based (co)polymers having a branched structure and propylene-based (co)polymers having a high molecular weight component are also preferably used. Examples of such propylene-based (co)polymers include crystalline propylene homopolymers obtained by irradiating linear polypropylene-based resins with radiation, linear polypropylene-based resins such as propylene homopolymers, block copolymers and random copolymers, conjugated diene compounds, and crystalline propylene-based (co)polymers obtained by melt-mixing radical polymerization initiators. Among these, those having a branched structure are preferred.
[0052] The method for producing the modified polypropylene exhibiting strain hardening properties of component (C) is not particularly limited, and for example, a known polymerization method using a known olefin polymerization catalyst can be applied, and one example of such a method is a multi-stage polymerization method using a Ziegler-Natta catalyst. This multi-stage polymerization method can be a slurry polymerization method, a solution polymerization method, a bulk polymerization method, a gas phase polymerization method, or the like, and two or more of these methods can be combined to produce the polypropylene.
[0053] The modified polypropylene exhibiting strain hardening properties as component (C) used in the present invention preferably has a long chain branched structure.
[0054] The long chain branched structure is described in detail in Macromol. Chem. Phys. 2003, vol. 204, 1738, as follows. The propylene-based (co)polymer having a long-chain branched structure has a specific branched structure as shown in the following structural formula (1). In the structural formula (1), Ca, Cb, and Cc represent methylene carbons adjacent to the branched carbons, Cbr represents a methine carbon at the base of the branched chain, and P 1 , P 2 , P 3 represents a propylene (co)polymer residue. P 1 , P 2 , P 3 may itself contain a branched carbon (Cbr) other than the Cbr depicted in structural formula (1).
[0055] [ka]
[0056] Such a branched structure is 13Identified by C-NMR analysis. The assignment of each peak can be referred to the description in Macromolecules, Vol. 35, No. 10, 2002, pp. 3839-3842. That is, three methylene carbons (Ca, Cb, Cc) are observed at 43.9-44.1 ppm, 44.5-44.7 ppm, and 44.7-44.9 ppm, respectively, and a methine carbon (Cbr) is observed at 31.5-31.7 ppm. The methine carbon observed at 31.5-31.7 ppm may be hereinafter abbreviated as branched methine carbon (Cbr). It is characterized by the fact that the three methylene carbons adjacent to the branched methine carbon Cbr are observed to be separated into three diastereotopic unequal groups.
[0057] 13 Such branched chains as assigned by C-NMR indicate propylene-based (co)polymer residues having 5 or more carbon atoms branched from the main chain of a propylene-based (co)polymer, and can be distinguished from branches having 4 or less carbon atoms by the difference in the peak positions of the branched carbons. Therefore, in the present invention, the presence or absence of a long-chain branched structure can be determined by confirming the peak of this branched methine carbon. In addition, in the present invention 13 The method for measuring C-NMR is as follows.
[0058] ( 13 C-NMR measurement method) 200 mg of sample was dissolved in an NMR sample tube with an inner diameter of 10 mm together with 2.4 ml of o-dichlorobenzene / deuterated bromide benzene (C6D5Br) = 4 / 1 (volume ratio) and hexamethyldisiloxane, a chemical shift standard substance. 13 Perform C-NMR measurement. 13 C-NMR measurements are performed using a Bruker Biospin AV400M NMR instrument equipped with a 10 mm diameter cryoprobe. The measurement was performed at a sample temperature of 120°C using the proton complete decoupling method. Other conditions were as follows. Pulse angle: 90° Pulse interval: 4 seconds Accumulation count: 20,000 times The chemical shift was set to 1.98 ppm for the peak of the methyl carbon of hexamethyldisiloxane, and the chemical shifts of peaks due to other carbons were based on this. The peak near 44 ppm can be used to calculate the amount of long chain branching.
[0059] The modified polypropylene having a long chain branched structure according to the present invention is 13 The amount of long chain branches quantified from a peak near 44 ppm in the C-NMR spectrum is preferably 0.01 / 1000 total propylene (per 1000 total skeletal carbons) or more, more preferably 0.03 / 1000 total propylene or more, even more preferably 0.05 / 1000 total propylene or more, and preferably 1.00 / 1000 total propylene or less, more preferably 0.50 / 1000 total propylene or less, even more preferably 0.30 / 1000 total propylene or less. Within this range, a polypropylene-based resin with no or little gel and high strain hardening can be obtained.
[0060] In addition, the modified polypropylene having a long chain branching structure according to the present invention has a branching index g', which is known as a direct index of long chain branching, in absolute molecular weight Mabs of 1 million, and the lower limit is preferably 0.3 or more, 0.55 or more, 0.75 or more, and 0.78 or more, and the upper limit is preferably less than 1.0, 0.98 or less, 0.96 or less, and 0.95 or less. The above lower limit and upper limit can be any combination. When the branching index g' is in a range between any of the above preferred lower limits and any of the above preferred upper limits, a highly crosslinked component is not formed, which is preferable in terms of molded appearance. The most suitable range of the branching index g' in the present invention is 0.78 or more and 0.95 or less.
[0061] The branching index g' is known as a direct index of long chain branching. The branching index g' is explained in detail in "Developments in Polymer Characterization-4" (JV Dawkins ed. Applied Science Publishers, 1983), and its definition is as follows: Branching index g': [η]br / [η]lin [η]br: Intrinsic viscosity of polymer (br) with long chain branching structure [η]lin: Intrinsic viscosity of a linear polymer with the same molecular weight as the polymer (br)
[0062] As is clear from the above definition, when the branching index g' is a value smaller than 1, it is determined that a long chain branched structure is present, and the more long chain branched structures there are, the smaller the branching index g' becomes.
[0063] The branching index g' can be obtained as a function of the absolute molecular weight Mabs by using GPC equipped with a light scattering meter and a viscometer as detectors. The method for measuring the branching index g' in the present invention is described in detail in JP2015-40213A, but is as follows.
[0064] <Measurement method> GPC: Alliance GPCV2000 (Waters) Detectors: Listed in order of connection Multi-angle laser light scattering detector (MALLS): DAWN-E (Wyatt Technology) Differential Refractometer (RI): GPC included Viscometer: GPC included Mobile phase solvent: 1,2,4-trichlorobenzene (Irganox 1076 added at a concentration of 0.5 mg / mL) Mobile phase flow rate: 1mL / min Column: Tosoh GMHHR-H(S) HT, 2 columns connected Sample injection temperature: 140℃ Column temperature: 140℃ Detector temperature: All 140℃ Sample concentration: 1mg / mL Injection volume (sample loop volume): 0.2175 mL
[0065] <Analysis method> The absolute molecular weight (Mabs), the root mean square radius of gyration (Rg) obtained from the multi-angle laser light scattering detector (MALLS), and the intrinsic viscosity ([η]) obtained from the Viscometer are calculated using the data processing software ASTRA (version 4.73.04) attached to the MALLS, with reference to the following literature. References: 1. “Developments in Polymer Characterization-4” (JV Dawkins ed. Applied Science Publishers, 1983. Chapter 1.) 2.Polymer, 45, 6495-6505(2004) 3.Macromolecules, 33, 2424-2436(2000) 4.Macromolecules, 33, 6945-6952(2000)
[0066] Such modified polypropylene having a long chain branch structure and exhibiting strain hardening properties is produced by a method using a macromer copolymerization method in which a long chain branch structure is formed during polymerization. Examples of this method include those disclosed in JP-T-2001-525460, JP-A-10-338717, JP-T-2002-523575, JP-A-2009-57542, JP-A-05027353, and JP-A-10-338717. In particular, the macromer copolymerization method of JP-T-2009-57542 is suitable for the present invention.
[0067] The modified polypropylene exhibiting strain hardening properties as component (C) may be used alone or in any combination and ratio of two or more kinds.
[0068] As the modified polypropylene exhibiting strain hardening properties of component (C), many different grades are commercially available from manufacturers both in Japan and overseas, and these commercially available products can be used. Commercially available products include, for example, Prim Polypro (registered trademark) manufactured by Prime Polymer Co., Ltd., Sumitomo Noblen (registered trademark) manufactured by Sumitomo Chemical Co., Ltd., polypropylene block copolymer manufactured by SunAllomer Co., Ltd., Novatec (registered trademark) PP manufactured by Japan Polypropylene Corporation, WAYMAX (registered trademark) manufactured by Japan Polypropylene Corporation, Moplen (registered trademark) manufactured by LyondellBasell Co., Ltd., ExxonMobil PP manufactured by ExxonMobil Co., Ltd., Formolene (registered trademark) manufactured by Formosa Plastics Co., Ltd., Borealis PP manufactured by Borealis Co., Ltd., SEETEC PP manufactured by LG Chemical Co., Ltd., ASI POLYPROPYLENE manufactured by A. Schulman Co., Ltd., INEOS PP manufactured by INEOS Olefins & Polymers Co., Ltd., Braskem PP manufactured by Braskem Co., Ltd., Sumsung Total manufactured by SAMSUNG TOTAL PETROCHEMICALS Co., Ltd., Sabic (registered trademark) PP manufactured by Sabic Co., Ltd., and TOTAL PETROCHEMICALS manufactured by TOTAL PETROCHEMICALS Co., Ltd. Polypropylene, and YUPLENE (registered trademark) manufactured by SK Corp. Among these, Waymax is preferably used as a polypropylene having a long chain branching structure and exhibiting strain hardening properties.
[0069] <Component (D): Unsaturated silane compound> The unsaturated silane compound of component (D) used in the present invention is not limited, but an unsaturated silane compound represented by the following formula (1) is preferably used. RSi(R')3 (1)
[0070] In the above formula (1), R is an ethylenically unsaturated hydrocarbon group, and R' are each independently a hydrocarbon group having 1 to 10 carbon atoms or an alkoxy group having 1 to 10 carbon atoms, and at least one of the R' is an alkoxy group having 1 to 10 carbon atoms.
[0071] In formula (1), R is preferably an ethylenically unsaturated hydrocarbon group having 2 to 10 carbon atoms, and more preferably an ethylenically unsaturated hydrocarbon group having 2 to 6 carbon atoms. Specific examples include alkenyl groups such as vinyl, propenyl, butenyl, and cyclohexenyl.
[0072] In formula (1), R' is preferably a hydrocarbon group having 1 to 6 carbon atoms or an alkoxy group having 1 to 6 carbon atoms, more preferably a hydrocarbon group having 1 to 4 carbon atoms or an alkoxy group having 1 to 4 carbon atoms. At least one of R' is preferably an alkoxy group having 1 to 6 carbon atoms, more preferably an alkoxy group having 1 to 4 carbon atoms. The hydrocarbon group having 1 to 10 carbon atoms of R' may be any of an aliphatic group, an alicyclic group, and an aromatic group, but is preferably an aliphatic group. The alkoxy group having 1 to 10 carbon atoms of R' may be any of a straight-chain, branched, and cyclic group, but is preferably a straight-chain or branched group. When R' is a hydrocarbon group, specific examples thereof include alkyl groups such as methyl, ethyl, isopropyl, t-butyl, n-butyl, i-butyl, and cyclohexyl groups, and aryl groups such as phenyl groups. When R' is an alkoxy group, specific examples include a methoxy group, an ethoxy group, an isopropoxy group, and a β-methoxyethoxy group.
[0073] When the unsaturated silane compound is represented by the above formula (1), at least one of the three R's is an alkoxy group, preferably two R's are alkoxy groups, and more preferably all R's are alkoxy groups.
[0074] As the unsaturated silane compound, among those represented by formula (1), vinyltrialkoxysilanes such as vinyltrimethoxysilane, vinyltriethoxysilane, and propenyltrimethoxysilane are preferable. This is because the vinyl group allows the modification of component (B) to the ethylene-α-olefin copolymer, and the alkoxy group promotes the crosslinking reaction described below. That is, the alkoxy group introduced by graft modification to the ethylene-α-olefin copolymer with the unsaturated silane compound reacts with water in the presence of a silanol condensation catalyst to hydrolyze and generate a silanol group, and the silanol groups are dehydrated and condensed with each other, resulting in the bonding of the ethylene-α-olefin copolymers to each other and the crosslinking reaction. These unsaturated silane compounds may be used alone or in combination of two or more.
[0075] <Component (E): Peroxide> Examples of the peroxide of component (E) include organic peroxides belonging to the groups of hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxy esters, and ketone peroxides. Specific examples include the following:
[0076] The hydroperoxide group includes cumene hydroperoxide, tertiary butyl hydroperoxide, etc., the dialkyl peroxide group includes dicumyl peroxide, ditertiary butyl peroxide, 2,5-dimethyl-2,5-ditertiary butyl peroxyhexane, 2,5-dimethyl-2,5-ditertiary butyl peroxyhexyne-3, di(2-tertiary butyl peroxy isopropyl)benzene, etc., the diacyl peroxide group includes lauryl peroxide, benzoyl peroxide, etc., the peroxy ester group includes tertiary peroxy acetate, tertiary butyl peroxy benzoate, tertiary butyl peroxy isopropyl carbonate, etc., and the ketone peroxide group includes cyclohexanone peroxide, etc. These organic peroxides may be used alone or in combination of two or more kinds.
[0077] When used in combination with the crosslinking aid (component (F)) described below, a radical generator having a high thermal decomposition temperature is preferred. From this viewpoint, di-tert-butyl peroxide, di(2-tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and dicumyl peroxide are preferred.
[0078] <Component (F): Crosslinking aid> Examples of the crosslinking aid of component (F) include silicon hydride compounds such as metrohydrogen silicon, peroxide aids such as sulfur, p-quinone dioxime, p-dinitrosobenzene, 1,3-diphenyl guanidine, etc.; polyfunctional vinyl compounds such as divinylbenzene, triallyl cyanurate, triallyl isocyanurate, diallyl phthalate, etc.; polyfunctional (meth)acrylate compounds such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, allyl (meth)acrylate, etc.; compounds having a bismaleimide structure such as N,N'-m-phenylene bismaleimide and N,N'-m-toluylene bismaleimide; trimethylolpropane, trimethylolpropane trimethacrylate, tin chloride (SnCl2), etc. Among these, polyfunctional vinyl compounds such as divinylbenzene, triallyl cyanurate, triallyl isocyanurate, and diallyl phthalate, and polyfunctional (meth)acrylate compounds are preferred.
[0079] As another crosslinking aid, a phenol resin can be used, such as alkylphenol formaldehyde or brominated alkylphenol formaldehyde.
[0080] These crosslinking assistants may be used alone or in any combination and ratio of two or more kinds.
[0081] <Component (G): Softener> The modified elastomer composition of the present invention may contain a softener as component (G) from the viewpoints of increasing flexibility and improving processability, flowability and oil resistance.
[0082] Examples of component (G) include mineral oil-based rubber softeners and synthetic resin-based rubber softeners. Among these, mineral oil-based rubber softeners are preferred from the standpoint of affinity with other components.
[0083] Mineral oil-based rubber softeners are generally mixtures of aromatic hydrocarbons, naphthenic hydrocarbons, and paraffinic hydrocarbons, and those with a paraffinic hydrocarbon carbon ratio of 50% by mass or more relative to the total carbon atoms are called paraffinic oils, those with a naphthenic hydrocarbon carbon ratio of 30-45% by mass are called naphthenic oils, and those with an aromatic hydrocarbon carbon ratio of 35% by mass or more are called aromatic oils. Among these, liquid hydrocarbon-based rubber softeners that are liquid at room temperature (23±2°C) are preferred as softeners, and liquid paraffinic oils that are liquid at room temperature are more preferred. By using a liquid hydrocarbon-based rubber softener as a softener, the flexibility and elasticity of the modified elastomer composition of the present invention can be increased, and the processability and flowability tend to be dramatically improved.
[0084] The paraffinic oil is not particularly limited, but has a kinematic viscosity at 40°C of usually 10 cst (centistokes) or more, preferably 20 cSt or more, and usually 800 cSt or less, preferably 600 cSt or less. In addition, the pour point is usually -40°C or more, preferably -30°C or more, and 0°C or less, and is preferably used. In addition, the pour point is usually -40°C or more, preferably -30°C or more, and 0°C or less, and is preferably used. In addition, the flash point (COC) is usually 200°C or more, preferably 250°C or more, and usually 400°C or less, preferably 350°C or less, and is preferably used.
[0085] The softening agent of component (G) may be used alone or as two or more kinds in any combination and in any ratio.
[0086] In addition, when an oil-extended type is used as the aforementioned component (A), the hydrocarbon-based rubber softener introduced into the elastomer composition as a mixture of the oil-extended ethylene-α-olefin-non-conjugated diene copolymer rubber and the hydrocarbon-based rubber softener also corresponds to the softener of component (G). In this case, a separate softener may be added as component (G), or a separately added softener may be used. When a softener is added separately, the hydrocarbon-based rubber softener contained in the oil-extended component (A) and the separately added softener may be the same or different.
[0087] <Component (H): Silanol condensation catalyst> By blending component (H), a silanol condensation catalyst, with the modified elastomer composition of the present invention, the composition can undergo an intermolecular crosslinking reaction, and silanol groups are generated by hydrolysis through reaction with water. The silanol groups then undergo dehydration condensation with each other, progressing the crosslinking reaction, and the modified elastomers are bonded together to generate a crosslinked elastomer composition with excellent heat resistance.
[0088] Examples of silanol condensation catalysts of component (H) that can be used in the present invention include one or more compounds selected from the group consisting of metal organic acid salts, titanates, borates, organic amines, ammonium salts, phosphonium salts, inorganic and organic acids, and inorganic acid esters.
[0089] Examples of metal organic acid salts include dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin diacetate, dibutyltin dioctoate, stannous acetate, stannous octoate, cobalt naphthenate, lead octoate, lead naphthenate, zinc octoate, zinc caprylate, iron 2-ethylhexanoate, iron octoate, iron stearate, etc. Examples of titanates include tetrabutyl titanate, tetranonyl titanate, bis(acetylacetonitrile)di-isopropyl titanate, etc. Examples of organic amines include ethylamine, dibutylamine, hexylamine, triethanolamine, dimethyl soya amine, tetramethylguanidine, pyridine, etc. Examples of ammonium salts include ammonium carbonate, tetramethylammonium hydroxide, etc. Examples of phosphonium salts include tetramethylphosphonium hydroxide, etc. Examples of inorganic acids and organic acids include sulfuric acid, hydrochloric acid, acetic acid, stearic acid, maleic acid, toluenesulfonic acid, alkylnaphthylsulfonic acid, and other sulfonic acids, etc. Examples of inorganic acid esters include phosphoric acid esters, etc.
[0090] Of these, preferred are metal organic acid salts, sulfonic acids, and phosphates, and more preferred are metal carboxylates of tin, such as dioctyltin dilaurate, alkylnaphthylsulfonic acids, and ethylhexyl phosphate.
[0091] The above-mentioned silanol condensation catalysts may be used alone or in combination of two or more.
[0092] The silanol condensation catalyst is preferably used as a masterbatch in which a polyolefin and the silanol condensation catalyst are blended together. Examples of polyolefins that can be used in the masterbatch include polyethylene, polypropylene, and ethylene-α-olefin copolymers.
[0093] Examples of polyethylene include (branched or linear) ethylene homopolymers such as low-, medium-, and high-density polyethylenes; ethylene-α-olefin copolymers such as ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-4-methyl-1-pentene copolymers, ethylene-1-hexene copolymers, and ethylene-1-octene copolymers; and ethylene-based copolymer resins such as ethylene-vinyl acetate copolymers, ethylene-(meth)acrylic acid copolymers, and ethylene-(meth)acrylic acid ester copolymers. Among these, ethylene-α-olefin copolymers such as ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-4-methyl-1-pentene copolymers, ethylene-1-hexene copolymers, and ethylene-1-octene copolymers are preferred.
[0094] Among these, in the present invention, high-pressure low-density polyethylene, high-density polyethylene, and ethylene-α-olefin copolymers, which have an excellent balance between heat resistance and strength, are preferred. As the ethylene-α-olefin copolymer, ethylene-α-olefin copolymers such as ethylene-1-butene copolymer, ethylene-4-methyl-1-pentene copolymer, ethylene-1-hexene copolymer, and ethylene-1-octene copolymer are more preferred, and the ethylene-α-olefin copolymer is more preferably a copolymer of 2 to 60% by mass of one or more α-olefins and 40 to 98% by mass of ethylene. For the master batch of the silanol condensation catalyst, only one of these polyolefins may be used, or two or more may be blended and used.
[0095] When the silanol condensation catalyst is used as a masterbatch in which a polyolefin and the silanol condensation catalyst are blended, the content of the silanol condensation catalyst in the masterbatch is not particularly limited, but is usually preferably about 0.1 to 5.0 mass %.
[0096] As the silanol condensation catalyst-containing masterbatch, a commercially available product can be used, for example, "LZ082" or "LZ033" manufactured by Mitsubishi Chemical Corporation.
[0097] <Mixing ratio> The modified elastomer composition of the present invention preferably contains 5 to 40 parts by mass of component (A), 30 to 90 parts by mass of component (B), and 5 to 30 parts by mass of component (C) in a total amount of 100 parts by mass. When the content of component (A) is greater than the upper limit and the content of components (B) and (C) is less than the lower limit, the surface appearance tends to be inferior. Conversely, when the content of component (A) is less than the lower limit and the content of components (B) and (C) is greater than the upper limit, the surface appearance tends to be poor. If the content of component (B) is greater than the upper limit and the content of components (A) and (C) is less than the lower limit, blocking tends to become severe. Conversely, if the content of component (B) is less than the lower limit and the content of components (A) and (C) is greater than the upper limit, compression set tends to deteriorate. When the content of component (C) is greater than the upper limit and the content of components (A) and (B) is less than the lower limit, the compression set tends to deteriorate. Conversely, when the content of component (C) is less than the lower limit and the content of components (A) and (B) is greater than the upper limit, the moldability and surface appearance tend to deteriorate.
[0098] From such viewpoints, the proportion of component (A) in 100 parts by mass in total of components (A), (B) and (C) is more preferably 10 to 30 parts by mass, and even more preferably 12 to 25 parts by mass, the proportion of component (B) is more preferably 35 to 85 parts by mass, and even more preferably 40 to 80 parts by mass, and the proportion of component (C) is more preferably 5 to 25 parts by mass, and even more preferably 5 to 20 parts by mass.
[0099] The content of component (D) relative to the total of 100 parts by mass of components (A), (B), and (C) is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 5 parts by mass, and even more preferably 0.1 to 3 parts by mass, from the viewpoint of sufficiently proceeding with the crosslinking reaction. The content of component (E) is preferably 0.01 to 3 parts by mass relative to 100 parts by mass of the total of components (A), (B), and (C). From the viewpoints of obtaining a sufficient crosslinking reaction and maintaining a smooth molded appearance, the content is more preferably 0.05 to 2 parts by mass, and even more preferably 0.1 to 1 part by mass.
[0100] When the modified elastomer composition of the present invention contains component (F), the content of component (F) is preferably 0.001 to 2 parts by mass, and more preferably 0.003 to 1 part by mass, relative to 100 parts by mass in total of components (A), (B), and (C), from the viewpoints of economy and obtaining a sufficient crosslinking reaction.
[0101] In addition, when the modified elastomer composition of the present invention contains component (G), the content of component (G) (when an oil-extended type is used as component (A), the content of the hydrocarbon-based rubber softener in component (A) is included) is preferably 0.5 to 200 parts by mass relative to 100 parts by mass of the total of components (A), (B), and (C). If the content of component (G) is less than the lower limit, the effect of improving flexibility, fluidity, and oil resistance by component (G) cannot be sufficiently obtained, and if the content exceeds the upper limit, there is a risk of bleeding out from the surface. From this viewpoint, the content of component (G) is more preferably 1 to 100 parts by mass, and even more preferably 5 to 80 parts by mass relative to 100 parts by mass of the total of components (A), (B), and (C).
[0102] When the silanol condensation catalyst of component (H) is added to the modified elastomer composition of the present invention to cause a crosslinking reaction, the amount of the catalyst is not particularly limited, but is preferably 0.001 to 0.5 parts by mass, and more preferably 0.001 to 0.1 parts by mass, relative to 100 parts by mass of the modified elastomer composition of the present invention excluding component (H). When the amount of the silanol condensation catalyst added is equal to or more than the lower limit, the crosslinking reaction proceeds sufficiently and heat resistance tends to be good, which is preferable, and when it is equal to or less than the upper limit, premature crosslinking is unlikely to occur in the extruder, and roughness of the strand surface and product appearance tends to be unlikely to occur.
[0103] <Other ingredients> In addition to the above components, the modified elastomer composition of the present invention may contain other components such as various additives, fillers, resins and elastomers other than components (A) to (C), etc., within the range that does not impair the effects of the present invention.
[0104] Examples of additives include heat stabilizers, ultraviolet absorbers, light stabilizers, antioxidants, antistatic agents, crystal nucleating agents, rust inhibitors, viscosity modifiers, foaming agents, lubricants, and pigments. Of these, it is preferable to add an antioxidant, particularly a phenol-based antioxidant, a sulfur-based antioxidant, or a phosphorus-based antioxidant. It is preferable to add the antioxidant in an amount of 0.1 to 1% by mass based on 100% by mass of the modified elastomer composition of the present invention.
[0105] Examples of other resins include polyolefin resins, polyester resins, polycarbonate resins, polymethyl methacrylate resins, rosin and its derivatives, terpene resins, petroleum resins and their derivatives, alkyd resins, alkylphenol resins, terpene phenol resins, coumarone-indene resins, synthetic terpene resins, alkylene resins, olefin elastomers other than components (A) to (C), polyamide elastomers such as polyamide-polyol copolymers, polyvinyl chloride elastomers, polybutadiene elastomers, styrene elastomers, hydrogenated products thereof, products modified with acid anhydrides or the like to introduce polar functional groups, and products obtained by grafting, randomly and / or block copolymerizing other monomers.
[0106] <Production and molding of modified elastomer composition> The modified elastomer composition of the present invention can be produced by mechanically mixing two kinds of copolymers, components (A) and (B), modified polypropylene exhibiting strain hardening, component (C), unsaturated silane compound, component (D), peroxide, crosslinking aid, softener, other components, etc., by a known method, for example, Henschel mixer, V blender, tumbler blender, etc., and then mechanically melt-kneading by a known method. For this melt-kneading, a general melt-kneading machine such as a Banbury mixer, various kneaders, single-screw or twin-screw extruder, etc. can be used. In addition, as shown in the examples below, when the composition of the present invention is produced by kneading with a single-screw or twin-screw extruder, etc., melt-kneading can be performed in a heated state of usually 120 to 240 ° C, preferably 120 to 220 ° C.
[0107] In the modified elastomer composition of the present invention, the above-mentioned silanol condensation catalyst is blended, and the composition is molded by various molding methods such as extrusion molding, injection molding, press molding, etc., and then exposed to a water atmosphere to promote the crosslinking reaction between the silanol groups, thereby forming a crosslinked elastomer composition. Various conditions can be adopted for the method of exposing the composition to a water atmosphere, and examples of the method include a method of leaving the composition in air containing moisture, a method of blowing air containing water vapor, a method of immersing the composition in a water bath, and a method of spraying warm water in a mist form.
[0108] In this case, the hydrolyzable alkoxy groups derived from the unsaturated silane compounds used for the graft modification of components (A) to (C) react with water in the presence of a silanol condensation catalyst and are hydrolyzed to generate silanol groups. The silanol groups then undergo dehydration condensation with each other, causing a crosslinking reaction to proceed, and the modified elastomers bond together to generate a crosslinked elastomer composition.
[0109] The rate at which the crosslinking reaction proceeds depends on the conditions of exposure to the water atmosphere, but typically, the temperature range is 0 to 130°C, and the exposure time is within the range of 5 minutes to 1 week. Particularly preferred conditions are a temperature range of 40 to 90°C and a time range of 30 minutes to 24 hours. When using air containing moisture, the relative humidity is selected from the range of 1 to 100%.
[0110] The degree of crosslinking of the crosslinked elastomer composition thus obtained can be adjusted by changing the type and amount of the silanol condensation catalyst, the crosslinking conditions (temperature, time), and the like.
[0111] <Application> The applications of the modified elastomer composition and crosslinked elastomer composition of the present invention are not particularly limited, and they can be suitably used as automobile parts such as glass run channels, weather strips, hoses, wiper blades, and grommets, construction and industrial parts such as packings, gaskets, cushions, anti-vibration rubber, and tubes, as well as other sports and miscellaneous goods, medical parts, food parts, home appliance parts, and wire coating materials. EXAMPLES
[0112] Hereinafter, specific aspects of the present invention will be described in more detail using examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the present invention. Note that the values of various manufacturing conditions and evaluation results in the following examples are meant as preferred upper or lower limit values in the embodiments of the present invention, and the preferred range may be a range defined by a combination of the above-mentioned upper or lower limit values and the values of the following examples or values of the examples.
[0113] In the following examples and comparative examples, the raw materials used in the preparation of the elastomer compositions and the methods for evaluating the obtained elastomer compositions are as follows.
[0114] [raw materials] The raw materials used in the following Examples and Comparative Examples are as follows.
[0115] <Oil-extended ethylene-α-olefin-non-conjugated diene copolymer rubber> (A-1): Mitsui EPT (registered trademark) 3072EPM (manufactured by Mitsui Chemicals, Inc.) Metallocene-catalyzed oil-extended EPDM Non-conjugated diene: 5-ethylidene-2-norbornene Diene content: 5.4% by mass Ethylene unit content: 64% by mass Mooney viscosity: 51ML (1 minute preheating and 4 minutes after rotation) 125℃
[0116] <Ethylene / α-olefin copolymer> (B-1): Engage (registered trademark) XLT8677 (manufactured by The Dow Chemical Company) Ethylene / α-olefin copolymer α-Olefin: 1-Octene MFR (190℃, 21.2N): 1.0g / 10min Density: 0.87g / cm 3 End of melting point: 123℃
[0117] <Modified polypropylene exhibiting strain hardening properties> (C-1) WAYMAX MFX8 (Japan Polypropylene Corporation) MFR(230℃, 21.2N): 1g / 10min Melt tension: 24cN (230℃) Methylene carbons (Ca, Cb, Cc) and methine carbons (Cbr): observed Amount of long chain branching: 0.1 / 1000 total propylene (per 1000 total skeletal carbons) Branching index g' at absolute molecular weight of 1 million Mabs: 0.89 (C-2) WAYMAX MFX3 (Japan Polypropylene Corporation) MFR (230℃, 21.2N): 8g / 10min Melt tension: 5cN (230℃) Methylene carbons (Ca, Cb, Cc) and methine carbons (Cbr): observed Long chain branch amount: 0.2 / 1000 total propylene (per 1000 total skeletal carbons) Branching index g' at absolute molecular weight of 1 million Mabs: 0.87 (C-3) Novatec FY6 (Japan Polypropylene Corporation) MFR (230℃, 21.2N): 2.5g / 10min Melt tension: 2.4cN (230℃) Density (JIS K7112:1999): 0.90g / cm 3 Melting point: 160℃ (C-4) Adflex Q 300F (Lyondell Basell) MFR (230℃, 21.2N): 0.8g / 10min Melt tension: 7.8cN (230℃) Density (JIS K7112:1999): 0.88g / cm 3 Melting point: 163℃
[0118] <Unsaturated silane compounds> (D-1) Vinyltrimethoxysilane: KBM-1003 (manufactured by Shin-Etsu Chemical Co., Ltd.)
[0119] <Organic peroxide> (E-1) Di(2-tert-butylperoxyisopropyl)benzene: Perbutyl P (NOF Corporation) (E-2) Di-tertiary butyl peroxide: Perbutyl D (NOF Corporation) (E-3) 2,5-dimethyl-2,5-di(t-butylperoxy)hexane: Kayahexa AD40C (manufactured by Kayaku Akzo Co., Ltd., a mixture of 40% by mass of 2,5-dimethyl-2,5-di(t-butylperoxy)hexane and 60% by mass of organic filler)
[0120] <Crosslinking assistant> (F-1) Divinylbenzene (manufactured by Wako Pure Chemical Industries, Ltd., a mixture of 55% by mass of divinylbenzene and 45% by mass of ethylvinylbenzene)
[0121] <Softener> (G-1) Paraffin-based rubber softener: Diana (registered trademark) Process Oil PW90 (Idemitsu Kosan Co., Ltd., paraffin-based oil) Kinematic viscosity at 40°C: 95.54 cSt (centistokes) Pour point: -15℃ Flash point: 272℃
[0122] <Catalyst Masterbatch (MB)> (H-1) Silanol condensation catalyst MB: LZ033 (manufactured by Mitsubishi Chemical Corporation, linear low-density polyethylene containing 1.2% tin catalyst (dioctyltin dilaurate), MFR of low-density polyethylene: 2 g / 10 min (190 °C, 21.2 N load), density of low-density polyethylene: 0.92 g / cm 3 )
[0123] [Component (B-1): Measurement of melting end point of ethylene-α-olefin copolymer] Using a differential scanning calorimeter manufactured by Hitachi High-Tech Science Corporation, product name "DSC6220", in accordance with JIS K7121, approximately 5 mg of a sample was heated from 20°C to 200°C at a heating rate of 100°C / min, held at 200°C for 3 minutes, then cooled to -10°C at a cooling rate of 10°C / min, and then heated to 200°C at a heating rate of 10°C / min. The extrapolated peak end point (°C) was calculated from the thermogram measured when the sample was heated to 200°C at a heating rate of 10°C / min, and this was taken as the melting end point.
[0124] [Method for measuring the melt tension of components (C-1) to (C-4)] A Capillograph (manufactured by Toyo Seiki Seisakusho) equipped with an attachment for measuring melt tension and having a φ10 mm cylinder with a φ1 mm, 10 mm long orifice at its tip was used to measure the strand extruded from the die when the piston was lowered at 230°C with a piston descending speed of 10 mm / min. The strand was hung on a pulley equipped with a load cell 350 mm below and taken up at a speed of 1 m / min. After stabilization, the take-up speed was increased at a rate of reaching 200 m / min in 4 minutes, and the load applied to the pulley equipped with the load cell when the strand broke was measured. This measured load was taken as the melt tension. In Table 1, melt tension is abbreviated as "MT."
[0125] [Evaluation method] Various evaluation methods for the elastomer compositions in the examples and comparative examples are shown below.
[0126] (1)Surface hardness The obtained molded sheet was measured for Duro-A hardness (after 15 seconds) in accordance with JIS K6253 (Duro-A).
[0127] (2) Compression set The obtained molded sheet was measured in accordance with the standard of JIS K6262 under conditions of 70° C., 22 hours, and 25% compression.
[0128] (3) Extrusion appearance evaluation The obtained crosslinked elastomer composition was molded into a sheet having a thickness of 0.5 mm and a width of 35 mm using a single-screw extruder with a diameter of 20 mm and a full-flight screw at a cylinder setting temperature of 160°C to 200°C and a rotation speed of 20 rpm. The sheet was visually observed for the presence or absence of bumps on the surface and cut edges, and judged according to the following criteria. <Item> ◯: Good (the surface of the extrusion-molded sheet is smooth and free of convex defects) △: Fairly bad (fewer than 10 convex appearance defects on the surface of the extrusion-molded sheet per square meter) ×: Poor (10 or more convex defects in appearance on the surface of the extrusion-molded sheet per meter) <Ear crack resistance> 〇: Good (no cuts on either side of extrusion sheet, smooth) △: Fairly bad (there are about 1mm notches on both ends of the extrusion sheet) ×: Poor (There are cuts of 2 mm or more on both ends of the extrusion molding sheet)
[0129] [Example 1] The raw materials other than (G-1) were blended in the raw material blend shown in Table 1, and mixed for 1 minute with a Henschel mixer. Next, the obtained mixture was fed into the upstream feed port of a unidirectional twin-screw extruder (manufactured by Japan Steel Works, Ltd., product number: TEX30, L / D=46, number of cylinder blocks: 12) with a mass feeder. Then, component (G-1) was fed from the feed port in the middle of the extruder with a liquid addition pump, and the temperature was raised from the upstream to downstream parts in the range of 120 to 200 ° C. at a total discharge rate of 25 kg / h, melt kneading was performed, and the strands were cut to pelletize, producing a modified elastomer composition. 4 parts by mass of LZ033 (0.048 parts by mass as tin catalyst) was added as component (H-1) silanol condensation catalyst MB to 100 parts by mass of the obtained modified elastomer composition to obtain a crosslinked elastomer composition containing catalyst MB. The composition was injection molded into a sheet having a thickness of 2 mm, a width of 120 mm, and a length of 80 mm using an in-line screw type injection molding machine (Toshiba Machine Co., Ltd., product number: IS130) under conditions of an injection pressure of 50 MPa, a cylinder temperature of 220°C, and a mold temperature of 40°C. The sheet was then exposed to a thermo-hygrostat at 85°C and 85% RH for 24 hours to prepare a sheet for evaluation of surface hardness and compression set. The evaluation results of the elastomer composition of Example 1 are shown in Table 1.
[0130] [Examples 2 to 4 and Comparative Examples 1 to 5] The same treatment as in Example 1 was carried out except that the raw material composition was changed to that shown in Table 1, and pellets of the modified elastomer compositions of Examples 2 to 4 and Comparative Examples 1 to 5 were obtained, and each evaluation sheet was similarly molded and similarly evaluated. The results are shown in Table 1.
[0131] In Table 1, the amount of component (A-1) shown is not the actual amount, but the amount of EPDM alone of component (A-1) excluding the extender oil. Similarly, for component (E-3), the actual amount is not shown, but rather the amount of 2,5-dimethyl-2,5-di(t-butylperoxy)hexane alone (40% of the actual amount) in component (E-3), and for component (F-1), the actual amount is not shown, but rather the amount of divinylbenzene alone (55% of the actual amount) in component (F-1).
[0132] [Table 1]
[0133] [Evaluation Results] As shown in Table 1, all of Examples 1 to 4, which correspond to the elastomer compositions of the present invention, are excellent in compression set, moldability, and surface appearance (resistance to bumps and chipping). On the other hand, it is clear that the elastomer compositions of Comparative Examples 1 to 5 are insufficient in any one of compression set, moldability, and surface appearance (lumps, resistance to edge chipping). From these results, it was found that the elastomer composition of the present invention has good sealing properties and molded appearance. [Industrial Applicability]
[0134] The elastomer composition of the present invention is excellent in compression set, moldability, and surface appearance, and can therefore be widely and effectively used in various applications requiring these, such as automobile parts such as glass run channels and weather strips, civil engineering and building material parts such as construction gaskets, sporting goods, industrial parts, home appliance parts, medical parts, food parts, medical device parts, electric wires, miscellaneous goods, etc.
Claims
1. A modified elastomer composition comprising the following components (A) to (D) and grafted with the following component (E): the following component (A) is 5 to 40 parts by mass per 100 parts by mass in total of the following components (A), (B), and (C); the following component (B) is 30 to 90 parts by mass per 100 parts by mass in total of the following components (A), (B), and (C); the following component (C) is 5 to 30 parts by mass per 100 parts by mass in total of the following components (A), (B), and (C); and the following component (D) is 0.01 to 5 parts by mass per 100 parts by mass in total of the following components (A), (B), and (C), The amount of the following component (E) used is 0.01 to 3 parts by mass per 100 parts by mass of the total of the following components (A), (B) and (C), A modified elastomer composition comprising the following component (B), which has a melting end peak temperature of 115° C. or higher and 145° C. or lower as measured by a differential scanning calorimeter (DSC): Component (A): Ethylene / α-olefin / non-conjugated diene copolymer rubber Component (B): Ethylene / α-olefin copolymer rubber not containing non-conjugated diene units Component (C): Modified polypropylene exhibiting strain hardening and having a melt flow rate of 1.0 g / 10 min or more (230° C., load 21.2 N, JIS K7210 compliant) and a melt tension of 3.0 cN or more. Component (D): Unsaturated silane compound Component (E): Peroxide
2. The density of the component (B) is 0.880 g / cm 3 2. The modified elastomer composition of claim 1, wherein:
3. The modified elastomer composition according to claim 1 or 2, further comprising a component (F): a crosslinking auxiliary, in an amount of 0.001 to 2 parts by mass per 100 parts by mass of the total of the components (A), (B) and (C).
4. The modified elastomer composition according to any one of claims 1 to 3, wherein the component (D) is a compound represented by the following formula (1): RSi(R') 3 …(1) (wherein R is an ethylenically unsaturated hydrocarbon group, R' are each independently a hydrocarbon group having 1 to 10 carbon atoms or an alkoxy group having 1 to 10 carbon atoms, and at least one of the R' is an alkoxy group having 1 to 10 carbon atoms.)
5. The modified elastomer composition according to any one of claims 1 to 4, further comprising a component (G): a softener, in an amount of 0.5 to 200 parts by mass per 100 parts by mass of the total of the components (A), (B) and (C).
6. A crosslinked elastomer composition obtained by subjecting the modified elastomer composition according to any one of claims 1 to 5 to a crosslinking reaction with component (H): a silanol condensation catalyst.
7. A molded article made of the modified elastomer composition according to any one of claims 1 to 5 or the crosslinked elastomer composition according to claim 6.
Citation Information
Patent Citations
Mesa type high breakdown voltage semiconductor device
JP1978046285A
Process for producing thermoplastic elastomers containing partially crosslinked rubber concentrates
JP2005516098A
Dynamic-crosslinking thermoplastic elastomer composition
JP2018154707A
Modified polyolefin composition and crosslinked polyolefin composition
JP2018154815A
Thermoplastic elastomer composition
JP2018154821A
